The concept of the demonic in the thought of Paul Tillich and its root in J. Boehme, F.W. Schelling and the lutheran mysticism - Niño de Zepeda Gumucio, Rafael (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The concept of the demonic is one of the main contribution of Paul Tillich to the theological thought. It designate the ambiguous character of all existing realities, where there are the creative and destructive elements mixed in a simultaneous and confused way. I inquire, in this article, about the root of this concept. I investigate about the philosophical thought of J. Boehme and F.W. Schelling. Both philosophers explain the idea of the existence of two principles, one negative, destructive, symbolized by the image of the fire; and other positive, creative, symbolized by the light. Both are in god, in a dialectic creative relation, in which the positive one always overcomes. But in existence, both principles become relatively independent each other, loosing the divine harmony, bringing the evil and the ambiguity to the world. This philosophical reflexions contribute with the basics elements for the idea of the demonic , but I conclude that the fundamental root of the concept of the demonic in the thougt of Tillich comes from his protestant root: the Lutheran conscience of the world corruption caused by the human sin.